2022
DOI: 10.3201/eid2801.211466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hepatitis E Virus RNA Universal Blood Donor Screening, Catalonia, Spain, 2017‒2020

Abstract: Hepatitis E virus (HEV) is the major cause of acute viral hepatitis in several countries in Europe. HEV is acquired mainly by consumption of contaminated pork but can also be transmitted through blood transfusion. HEV infection is usually self-limited but can become persistent in immunocompromised persons. During the first 30 months of HEV RNA universal screening of blood donations in Catalonia, Spain, we identified 151 HEV RNA–positive donations (1/4,341 blood donations). Most infected donors reported consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
5
16
1
Order By: Relevance
“…As previous studies have reported seroprevalence geographical differences in France, it will be interesting to analyse the relationship between antibody prevalence and incidence data at the regional level after the introduction of universal HEV-RNA screening [11]. However, the rate of 0.059% HEV-RNA-positive blood donations estimated in our whole BD population is in line with the studies from Spain and Germany, suggesting the reliability of the adjustment [12,13]. Furthermore, although reinfections remain possible, we assumed that a given donor could not be infected more than once during the study period.…”
Section: Discussionsupporting
confidence: 82%
“…As previous studies have reported seroprevalence geographical differences in France, it will be interesting to analyse the relationship between antibody prevalence and incidence data at the regional level after the introduction of universal HEV-RNA screening [11]. However, the rate of 0.059% HEV-RNA-positive blood donations estimated in our whole BD population is in line with the studies from Spain and Germany, suggesting the reliability of the adjustment [12,13]. Furthermore, although reinfections remain possible, we assumed that a given donor could not be infected more than once during the study period.…”
Section: Discussionsupporting
confidence: 82%
“…The rate of HEV RNA positivity among blood donors varies greatly between countries worldwide, and variation is also high between European countries from 1:744 to 1:8636 [ 10 , 14 , 35 ]. The prevalence observed in our study is among the countries with fairly low rates, such as Ireland 1:4997 [ 19 ], Spain 1:4341 [ 24 ], Belgium 1:5448 [ 36 ], and Austria 1:8416 [ 37 ]. The observed rate in our study is below the overall EU rate of 1:3109 donations [ 16 ].…”
Section: Discussionmentioning
confidence: 80%
“…Several European countries have implemented screening of blood donors for HEV RNA based on a national risk assessment [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. There are also countries that have decided not to implement screening, e.g., Denmark, where transmission risk in a study in 2015 was found to be low [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…HEV RNA copies in plasma of infected patients were quantified at the Vall d’Hebron clinical laboratories with Cobas 6800 (Roche Diagnostics) and using a calibration curve based on the first World Health Organization International Standard for HEV RNA (Paul-Ehrlich-Institut code 6329/10), whereas viral loads in plasma of HEV BDs were determined at Banc de Sang i Teixits by in-house reverse transcription-PCR (RT-PCR) as previously described ( 52 ). All HEV isolates belonged to genotype 3 according to the genotyping method described by Bes et al ( 53 ). Plasma levels of alanine transaminase (ALT), aspartate transaminase (AST), and gamma-glutamyl transpeptidase (GGT) in HEV-infected patients and HEV BDs were analyzed at the Vall d’Hebron clinical laboratories or at a reference biochemistry laboratory, respectively.…”
Section: Methodsmentioning
confidence: 99%